Multicolor Electrochemiluminescence of Binary Microcrystals of Iridium and Ruthenium Complexes - Ding, Chun-Yun; Zhong, Yu-Wu (Chemistry, an Asian journal, 2024)
We here report the multicolor electrochemiluminescence (ECL) of binary microcrystals prepared from a blue-emissive iridium complex 1 and an orange-emissive ruthenium complex 2. These materials display a plate-like morphology with high crystallinity, as demonstrated by microscopic and powder X-ray diffraction analyses. Under light excitation, these microcrystals exhibit gradient emission color changes as a result of the efficient energy transfer between two complexes. When modified on glass carbon electrodes, these microcrystals exhibit tunable ECLs with varied emission colors including sky-blue, white, orange, and red, depending on the doping ratio of complex 2 and the applied potential. Furthermore, organic amines with different molecular sizes are used as the co-reactant to examine their influences on the ECL efficiency of the porous microcrystals of 1. The analysis on the luminance and RGB values of ECL suggests the existence of energy transfer in the generation of multicolor ECLs in these binary crystals.